The Effect of Price and Location on Patient Satisfaction (Survey of Outpatient Patients of Tata Sehat Clinic in Bandung) - Widiyanti, Maria; Oktini, Dede R; Amalia, Ima; Adwiyah, Rabiatul (Journal of Information System, Technology and Engineering, 2025)
In the healthcare industry, patient satisfaction is a major concern for healthcare providers, patient satisfaction is not only related to the quality of medical services provided but is also influenced by other factors such as price and location of healthcare services. This study aims to analyze the effect of Price and Location on Outpatient Satisfaction by taking a survey of Patients at the Tata Sehat Clinic in Bandung City. The data used in this study were taken from primary data, namely data directly taken by researchers by distributing questionnaires to patients of the Tata Sehat Clinic and secondary data, namely data on the number of patient visits from the Tata Sehat Clinic. Sampling was carried out using the non-probability sampling method with a total of 100 respondents. The independent variables in this study were price and location, while the dependent variable in this study was patient satisfaction. The results of the study using the T test (partial) showed that the price variable partially had a positive and significant effect on the patient satisfaction variable. The location variable also partially had a positive and significant effect on the patient satisfaction variable. The results of the study using the F test (simultaneous) showed that the price and location variables simultaneously had a positive and significant effect on the patient satisfaction variable. Multiple linear regression analysis obtained the following regression equation Y = 5.072 + 0.435X1 + 0.286X2. The results of the determination coefficient test (adjusted R square) value are0.521 this means that the price and location influences patient satisfaction by 52.1%, while the restby 47.9%influenced by other variables outside this research.